Conceptual Structures for STEM Research and Education 20th International Conference on Conceptual Structures, ICCS 2013, Mumbai, India, January 10-12, 2013. Proceedings - Pfeiffer, Heather D.; Ignatov, Dmitry I.; Poelmans, Jonas; Gadiraju, Nagarjuna; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 20th International Conference on Conceptual Structures, ICCS 2013, held in Mumbai, India, in January 2013. The 22 full papers presented were carefully reviewed and selected from 43 submissions for inclusion in the book. The volume also contains 3 invited talks. ICCS focuses on the useful representation and analysis of conceptual knowledge with research and business applications. It advances the theory and practice in connecting the user's conceptual approach to problem solving with the formal structures that computer applications need to bring their productivity to bear. Conceptual structures (CS) represent a family of approaches that builds on the successes of artificial intelligence, business intelligence, computational linguistics, conceptual modeling, information and Web technologies, user modeling, and knowledge management.
Syllogisms in Logic Teaching -- A Model to Compare and Manipulate Situations Represented as Semantically Labeled Graphs -- Analyzing Clusters and Constellations from Untwisting Shortened Links on Twitter Using Conceptual Graphs -- Taking SPARQL 1.1 Extensions Into Account in the SWIP System -- System Architecture to Implement a Conceptual Graphs Storage in an RDF Quad Store -- Medical Archetypes and Information Extraction Templates in Automatic Processing of Clinical Narratives -- Using Conceptual Structures in the Design of Computer-based Assessment Software -- Modeling Ontological Structures with Type Classes in Coq -- Parse Thicket Representation for Multi-sentence Search -- FCA-based Models and a Prototype Data Analysis System for Crowdsoursing Platforms -- The First-order Logical Environment -- Using Conceptual Graphs for Cross-Domain Inference in Context of Laws of Science -- Summarizing Conceptual Graphs for Automatic Summarization Task -- Model of Knowledge Representation Providing Processing Multidimensional Measurements in the Environment of Intelligent GIS -- Transformation of SBVR Business Rules to UML Class Model -- Concept Lattices of a Relational Structure -- Representing Median Networks with Concept Lattices -- Txt2vz: a New Tool for Generating Graph Clouds.
Keywords: Computer science; Computational complexity; Database management; Information storage and retrieval systems; Artificial intelligence; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Discrete Mathematics in Computer Science; Database Management; Information Storage and Retrieval; Pattern Recognition